Peranan Lembaga Kemasyarakatan dalam Membantu Tugas Lurah - Ryan Anggria Pratama; Askarmin Harun (JURNAL TRIAS POLITIKA, 2017)
AbstractThe underlying consideration of this research is that given the increasingly growing the urban village chief’s duty in the field of government, development and community empowerment, the presence and role of Social Institution is very much needed to assist the urban village chief’s duty in the implementation. This research was conducted in Bukit Cermin Urban Village Tanjungpinang City which is the best Urban Village of Riau Islands in the year 2015. This study aims to determine the role and constraints of Social Institutions in assisting the The urban village chief’s duty in the field of development in Bukit Cermin Urban Village of Tanjungpinang. The results of the study found that the role of Social Institutions in assisting the urban village chief in the development of Bukit Cermin Urban Village of Tanjungpinang includes educational inspirator, environmental facilitator, entrepreneurial motivator, order mediator and development initiator. Then that hamper the role of social institutions in assisting the urban village chief’s duty in the field of development such as lack of support from the local government, does not occur the process of good regeneration, and inequality in the coaching of social institutions. The authors argue that the obstacles that occur because the Regional Government of Tanjungpinang City just issued a Regional Regulation on Social Institutions in 2016, so that in previous years for the city of Tanjungpinang only refers directly to the Regulation of the Minister of Home Affairs of the Republic of Indonesia No. 5 of 2007 on Guidelines Setup  of Social Institutions without more specific rules. Keywords: roles, social institutions, development AbstrakPertimbangan yang mendasari penelitian ini adalah mengingat tugas lurah yang semakin bertambah dibidang pemerintahan, pembangunan dan pemberdayaan masyarakat, maka kehadiran dan peranan Lembaga Kemasyarakatan teramat sangat dibutuhkan guna membantu tugas lurah dalam penyelenggaraannya. Penelitian ini dilakukan di Kelurahan Bukit Cermin Kota Tanjungpinang yang merupakan Kelurahan terbaik se-Kepulauan Riau pada Tahun 2015. Peneltian ini bertujuan untuk mengetahui peranan dan hambatan lembaga kemasyarakatan dalam membantu tugas Lurah di bidang pembangunan di Kelurahan Bukit Cermin Kota Tanjungpinang. Hasil penelitian ditemukan bahwa peranan lembaga kemasyarakatan dalam membantu tugas lurah dibidang pembangunan di kelurahan bukit cermin kota Tanjungpinang meliputi Inspirator pendidikan, Fasilitator lingkungan, Motivator kewirausahaan, Mediator ketertiban, dan inisiator pembangunan. Kemudian yang menghambat peranan lembaga kemasyarakatan dalam membantu tugas lurah dibidang pembangunan seperti minimnya dukungan dari pemerintah daerah, tidak terjadi proses kaderisasi yang baik, dan ketidakmerataan dalam pembinaan lembaga kemasyarakatan. Hambatan itu terjadi dikarenakan Pemerintahan Daerah Kota Tanjungpinang baru mengeluarkan Peraturan Daerah tentang Lembaga Kemasyarkatan pada Tahun 2016, sehingga pada tahun-tahun sebelumnya untuk Kota Tanjungpinang hanya mengacu langsung pada Peraturan Menteri Dalam Negeri Republik Indonesia Nomor 5 Tahun 2007 tentang Pedoman Penataan Lembaga Kemasyarakatan tanpa peraturan lebih khusus Kata Kunci: peranan, lembaga kemasyarakatan, pembangunan